PENERAPAN SISTEM MERIT DALAM MANAJEMEN APARATUR SIPIL NEGARA DI LINGKUNGAN PEMERINTAH KOTA MAGELANG - Sutrisna, Sutrisna; Triputro, Widodo (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2024)
The merit system is an important factor in bureaucratic reform which aims to create ASN who are professional and have integrity to create government administration that is effective, efficient, transparent and free from political intervention. Independent assessment of the implementation of the merit system is a measuring tool to ensure the merit system is carried out in accordance with applicable regulations. BKPSDM Magelang Municipality has started implementing a merit system in personnel management since 2021, and continues to improve every year. This research aims to determine the extent to which the merit system is implemented by BKPSDM Magelang Municipality in personnel management. This research uses descriptive qualitative methods. Data/information collection techniques are carried out through interviews and document studies. Data analysis by means of data reduction, presentation and drawing conclusions. The research results show that BKPSDM Magelang Municipality has succeeded in achieving increased implementation of the merit system due to strong support and commitment from the leadership. However, BKPSDM Magelang Municipality needs to make improvements in budget allocation, commitment from agency leaders, and increase awareness and understanding of civil servants as well as synergy with stakeholders in order to implement a merit system in personnel management.